Classification of the semantic series of words adopted from French into English and its research - KH.Y.Olimov (Genius Journals, 2023)
This article is devoted to the modern development of the English language and the different theoretical views of scholars, as well as the importance of assimilation words.
Keywords: The role of the modern English; language